WASH facilities prevalence and determinants: Evidence from 42 developing countries - Rahut, Dil B.; Singh, Anjali; Sonobe, Tetsushi (Frontiers in Environmental Science, 2022)
Improved WASH facilities are crucial for reducing infectious diseases such as diarrhoea, malaria, dengue, worms, etc. However, a large proportion of households in developing countries lack basic WASH facilities. Therefore, the current paper uses the household data from 733,223 households in fourty two developing countries to explore the prevalence rate of basic WASH facilities. The result shows that access to basic drinking water is much better than access to other WASH facilities, such as basic sanitation and hygiene facilities. However, the prevalence of basic drinking water, basic sanitation, and basic hygiene varies across different regions and countries- low in Africa and South Asia. The multi-level regression model shows that households with better economic status and education and urban households are more likely to use basic WASH facilities. Further, women empowerment and already having one WASH practice are also positively associated with the adoption of other WASH facilities. The policy should aim at improving awareness about the benefit of WASH facilities through education, and it should also subsidize WASH facilities for poor households and those living in rural areas.